Determinants of Gender Willingness to Participate in Co-Management of Ecotorism Resources: The Case of Kisumu County - Mogoria, Naomi Apali; Olima, Washington H. A.; Gor, Christopher O. (My University, 2018)
Gender is one of the integral aspects that emerge in environmental resource management for ecotourism planning amongst various players. There are hardly any gender studies that have been carried out in Kisumu to consider the significance differences of gender division of roles within the community towards ecotourism as an important component of environmental resource management. The glaring gap that has emerged from these studies is gender equity framework for men and women to carry out environmental activities has either been left out, or minimally considered. This study’s objective was to examine differences in willingness of men and women to participate in environment based ecotourism activities in Kisumu County. The study was a qualitative study that used case study design. The study was conducted in Kisumu County, the sample are deduced through purposive. Purposive sampling was also used to identify key informants. Data was collected using key informant interviews, Focus Group Discussions, direct participant observation and review of secondary sources. Data analysis methods used were, Content Analysis and Force Field Analysis. The study findings revealed that there are intervening variables identified as Force Fields, which are external determinant factors that either catalyzed or impeded willingness to participate in ecotourism activities by men and women. Key recommendations of this study were: to enhance gender participation, there was need for: induction and targeted training modules; convene gender responsive meetings; skill enhancement training to reduce language barrier; exposure tours; gender needs- based financial and budgeting capacity building; strategize ecotourism as a top-notch income source and forge global-wide strategic networks and Private Public Partnerships (PPP)
Keywords: Ecotourism, Co-management, Environment Based Resources, Gender